Approximate solutions of the Boltzmann equation with infinitely many modes - Gordevskii, V. D.; Gukalov, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
For the nonlinear kinetic Boltzmann equation in the case of a model of hard spheres, we construct an approximate solution inthe form of a series of Maxwellian distributions with coefficient functions of time and the space coordinate. We establish thesufficient conditions for the coefficient functions and the values of hydrodynamic parameters appearing in the distributionthat enable us to make the analyzed deviation arbitrarily small.